Positivism in the Civil Law System: A Philosophical and Practical Inquiry for Indonesia - Muhamad Sirot; Zainal Arifin Hoessein (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
This article examines the role of legal positivism within the civil law system and its relevance to Indonesia's legal practice. Using a normative and literature review approach, this study highlights the philosophical foundations of positivism from Austin, Kelsen, and Hart, and analyzes its influence on the formalistic and legal certainty-oriented characteristics of civil law. Findings indicate that while positivism strengthens legal certainty, it often neglects substantive justice and social plurality. The article recommends an inclusive reinterpretation of positivism integrating justice and human rights values in Indonesia's legal context.   Keywords: Legal Positivism; Civil Law; Legal Certainty; Substantive Justice; Indonesian Law.